Effect of Shell Correction on the Decay Pattern and Half Life Times for Spontaneous Fission within the Collective Clusterization Approach - Bhatia, Shivangi (My University, 2019)
In this thesis, the role of shell corrections (δU) on the decay pattern and half life time of various parent nuclei particularly from 232U to 264Hs undergoing spontaneous fission in the ground state (T=0 MeV) has been analyzed using the Preformed Cluster-decay Model (PCM) which employs Collective Clusterization Approach of Quantum Mechanical Fragmentation Theory (QMFT) as its main tool. In this thesis, we have extended the work in which the spontaneous fission half life times were fitted using the neck-length parameter (ΔR) in the presence of shell correction energy δU. In present work, half life times excluding the shell correction energy are computed using same neck length. The effects of shell correction energy on the fragmentation potential, preformation probability and minimized charges of the fragments for the decay of various parent nuclei 232U to 264Hs are also analyzed.
Keywords: Spontaneous Fissopn; collective clusterization; preformed cluster decay model